2016
DOI: 10.1073/pnas.1519467113
|View full text |Cite
|
Sign up to set email alerts
|

Gene control of tyrosine kinase TIE2 and vascular manifestations of infections

Abstract: Ligands of the endothelial-enriched tunica interna endothelial cell kinase 2 (Tie2) are markedly imbalanced in severe infections associated with vascular leakage, yet regulation of the receptor itself has been understudied in this context. Here, we show that TIE2 gene expression may constitute a novel vascular barrier control mechanism in diverse infections. Tie2 expression declined rapidly in wide-ranging models of leak-associated infections, including anthrax, influenza, malaria, and sepsis. Forced Tie2 supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(99 citation statements)
references
References 58 publications
14
84
1
Order By: Relevance
“…Levels of phosphorylated (active) Tie2 were significantly decreased in endotoxemic mice at the early 3-hour time point compared with saline controls (Figure 3, G and H). The temporal profile of the Angpt-1/ Angpt-2 ratio in circulation (Supplemental Figure 2A) suggested that an early decline in Angpt-1 ( Figure 3I) contributed to reduced Tie2 signaling, which in turn, derepressed Angpt-2 ( Figure 3J), consistent with prior studies (19,(41)(42)(43)(44). To assess whether the loss of vascular quiescence indicated by reduced Tie2 signaling was more broadly manifest, we analyzed a panel of endothelial activation markers in plasma collected at 3 hours after LPS; PAI-1, von Willebrand factor (VWF), and soluble forms of endothelial adhesion molecules (sE-selectin and sVCAM-1) were all elevated at the early 3-hour time point (Supplemental Figure 2, B-E).…”
Section: 7supporting
confidence: 87%
See 2 more Smart Citations
“…Levels of phosphorylated (active) Tie2 were significantly decreased in endotoxemic mice at the early 3-hour time point compared with saline controls (Figure 3, G and H). The temporal profile of the Angpt-1/ Angpt-2 ratio in circulation (Supplemental Figure 2A) suggested that an early decline in Angpt-1 ( Figure 3I) contributed to reduced Tie2 signaling, which in turn, derepressed Angpt-2 ( Figure 3J), consistent with prior studies (19,(41)(42)(43)(44). To assess whether the loss of vascular quiescence indicated by reduced Tie2 signaling was more broadly manifest, we analyzed a panel of endothelial activation markers in plasma collected at 3 hours after LPS; PAI-1, von Willebrand factor (VWF), and soluble forms of endothelial adhesion molecules (sE-selectin and sVCAM-1) were all elevated at the early 3-hour time point (Supplemental Figure 2, B-E).…”
Section: 7supporting
confidence: 87%
“…As dysregulation of the Angpt/Tie2 pathway was associated with a prothrombotic state, we next studied microvascular thrombus formation in Tie2 +/-mice. Heterozygous mice are indistinguishable from wild-type (WT) littermates at baseline, but exhibit increased susceptibility to inflammation and infections (19,37,45). Unexpectedly, partial Tie2 deficiency alone was sufficient to enhance fibrin deposition independent of LPS ( Figure 5, A-E).…”
Section: 7mentioning
confidence: 97%
See 1 more Smart Citation
“…Reduced Ang2 gene dosage (31), ANG2 blocking antibodies (32), and ectopic ANG1 reduce sepsis-induced vascular leak and lung injury in mice (33). In comparison, mice expressing reduced Tie2 levels are more susceptible to LPS-induced endotoxemia (34,35). ANG2 inhibition also reduces the harmful inflammation associated with cardiac transplant rejection (36) and improves endothelial-pericyte interactions in diabetic retinopathy (37).…”
Section: Resultsmentioning
confidence: 99%
“…97 At present, Ang-2/Ang-1 ratios remain an excellent marker for severe disease, but whether this pathway contributes critically to human cerebral malaria or acute lung injury as seen in sepsis remains unclear. 98 Host-derived products released at the time of red blood cell rupture such as free heme and its parent compound, hemoglobin, have also been implicated in pediatric 99 and adult 100 severe malaria as well as in endothelial dysfunction in malaria. 101 Heme is known to disrupt endothelial barriers directly through induction of free radical generation and mitochondrial reactive oxygen species signaling in endothelial cells.…”
Section: Host Inflammatory Mediatorsmentioning
confidence: 99%